A mechanistic study of silica-etching by hot water. Issue 3 (19th December 2017) - Zhu, Zhijie; Zhang, Shumin; Li, Chaoran; Zhang, Jinpan; Yu, Jia; Du, Xuemin; He, Le; Zhang, Xiaohong
Abstract : The mechanism of silica etching by hot water is elucidated which allows the controlled synthesis of mesoporous silica nanostructures. Abstract : The etching of colloidal silica by hot water provides a green chemistry method for the preparation of mesoporous silica. Nevertheless, the reaction mechanism of this etching process has not been elucidated and its reproducibility is often questionable, which has hindered its widespread application in the preparation of mesoporous silica materials. Herein, we present a systematic study on the hot-water etching of sol–gel derived silica shells coated on α-Fe2 O3 particles. Transmission electron microscopy and infrared spectroscopy studies provide substantial evidence that colloidal silica with low hydrolysis and condensation degrees (or aging degrees) is preferentially etched by hot water. More importantly, we show that the aging degree of silica shells, which determines the etching rate, can be precisely tuned by controlling the sol–gel preparation time and the storage time in room-temperature water prior to hot-water etching. These results provide novel insights into the physicochemical properties of sol–gel derived colloidal silica and the mechanistic understanding of the reaction kinetics of silica etching by hot water.